Electronic and optical response of Cr-doped MoSe2 and WSe2: Compton measurements and first-principles strategies. (August 2017) - Kumar, Kishor; Heda, N.L.; Jani, A.R.; Ahuja, B.L.
Abstract: In this paper, we present energy bands, density of states and Mulliken's population (MP) data using the linear combination of atomic orbitals (LCAO) method. To compare the theoretical momentum densities, we have also employed 100 mCi 241 Am Compton spectrometer to measure the Compton profiles of Cr0.5 X0.5 Se2 (X=Mo and W). The experimental Compton data have been used to check the performance of various exchange and correlation energies for the present mixed dichalcogenides within the LCAO scheme. It is seen that CPs based on the hybridization of Hartree-Fock and density functional theory give a better agreement with the experimental data than other schemes employed in the present investigations. All theoretical approximations show an indirect band gap between the Γ and K points of the Brillouin zone. Further, equal-valence-electron-density scaled experimental data predict a more ionic character in Cr0.5 W0.5 Se2 than in Cr0.5 Mo0.5 Se2, which is in tune with our MP data. Going beyond the computation of electronic properties using LCAO, we have also reported accurate electronic and optical properties using the modified Becke-Johnson (mBJ) potential within the full potential augmented plane wave (FP-LAPW) method. Optical properties computed using the FP-LAPW-mBJ method show the feasibility of using both the mixed dichalcogenides in photovoltaic devices. Graphical abstract: Highlights: Observed indirect band gap (Γ and K points of BZ) using DFT calculations. Measured Compton profiles (CPs) of Cr0.5 X0.5 Se2 (X=Mo and W). Discussed bonding using EVED and Mulliken's population data. Compared experimental CPs with first-ever electron momentum density. FP-LAPW-mBJ based optical response shows photovoltaic properties.